Child Marriage and Intimate Partner Violence: An Examination of Individual, Community, and National Factors. Issue 21 (November 2022) - Hayes, Brittany E.; Protas, Michelle E.
Despite being a human rights violation, child marriage still takes place across the globe. Prior scholarship has shown early marriage to be associated with an increased risk of intimate partner violence (IPV). Drawing on data from the nationally representative Demographic and Health Surveys—conducted in developing and transitional nations where rates of child marriage tend to be higher—the current study provides a cross-national examination of individual-, community-, and national-level predictors of child marriage and their association with physical and emotional IPV. The sample of ever married women includes 281, 674 respondents across 46 developing and transitional nations. Findings reveal the prevalence of child marriage was largely consistent with worldwide estimates. Over half of the sample (59.97%) were over the age of 18 when they married and about 1 in 10 women were married at age 14 or younger. A later age at marriage, measured continuously, was associated with lower odds of physical and emotional IPV. When considering the 18 and over cutoff traditionally used to operationalize child marriage, the odds of physical and emotional IPV were lower for women who married over the age of 18 than women who were 14 and younger when they married. However, there was a confounding effect when considering age at marriage as 18 and over when community-level predictors were not included in the model estimating physical abuse. This underscores the need to consider the nested nature of respondents' experiences. Further, national legislation that protects against child marriage was not associated with risk of physical or emotional IPV. However, population size increased the odds of physical IPV and lowered the odds of emotional IPV. Such findings can be interpreted in light of opportunity theory and provide direction for prevention and intervention programming.